The Oxford Companion to American Theatre - Bordman, Gerald Martin; Hischak, Thomas S. (North American theatre online., 2004)
A guide to the American stage from its beginnings to the present. Includes entries on playwrights, plays, actors, directors, producers, songwriters, famous playhouses, dramatic movements, classic works, commercially successful plays, and foreign figures that have influenced American dramatic development.